2013
DOI: 10.26719/2013.19.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement and bullying among middle school students in North Africa

Abstract: Bullying, especially in developing countries, has not been much examined, especially the influence of parents on the risk of being bullied. The aim of this study was to determine whether active parenting is associated with reduced peer victimization among middle-school students in North Africa. A secondary analysis of data from more than 13 000 middle-school students who participated in the Global School-based Student Health Survey (GSHS) in Egypt, Libya, Morocco and Tunisia between 2006 and 2008, was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 21 publications
(46 reference statements)
1
27
2
2
Order By: Relevance
“…The final 38 reports provided quantitative estimates of prevalence of 1 or more types of violence against children occurring during the previous year. 17,10–15,1848…”
Section: Methodsmentioning
confidence: 99%
“…The final 38 reports provided quantitative estimates of prevalence of 1 or more types of violence against children occurring during the previous year. 17,10–15,1848…”
Section: Methodsmentioning
confidence: 99%
“…In GSHS surveys, nearly two-thirds of boys and from one-third to more than half of girls in Djibouti, Egypt, and Tunisia report being physically attacked in the past year; even larger proportions report being involved in a physical fight, with boys reporting higher levels than girls [92]. One to two-thirds of students in Egypt, Libya, Morocco, and Tunisia report being bullied, with boys typically reporting more peer victimization than girls [158]. An analysis of data from 27 countries found that compared with other regions, EMRO had the highest mean prevalence of any fighting (47%) and of frequent fighting (5%) [159].…”
Section: Armed Conflict and Interpersonal Violencementioning
confidence: 99%
“…At the individual level, for example, ability will be related to students' likelihood to being a top or bottom performer, and by standing out from average performers, they are more prone to be victims of bullying (Bishop, 2006). Within the family, lack of parental attention in a child's education (due to poor control, supervision or encouragement) can be both a source of lower achievement (Freeman and Viarengo, 2014) and a sign of not recognising the psychological effect of bullying on a child (Abdirahman et al, 2012). Thus, lack of parental educational investments are linked to children's achievement and non-cognitive outcomes which can be further set back by weak school policies and teaching approaches.…”
Section: Empirical Approachmentioning
confidence: 99%
“…The matched subsample analysis sheds light onto what elements might contribute to the success of anti-bullying programs for the region, this is after isolating other important mediating factors (e.g., family wealth, parental education, home supervision, type of school, dimension and infrastructure, teacher's qualifications) (Abdirahman et al, 2012;Benbenishty and Astor, 2011;Chaux et al, 2009;Konstantina and Pilios-Dimitris, 2010) which are likely to be correlated to bullying and achievement.…”
Section: Implications From the Matched Subsample Analysismentioning
confidence: 99%